ANALISIS PENGELOLAAN WISATA BERBASIS CHSE SEBAGAI DESTINASI WISATA PASCA PANDEMI DI PANTAI BALEKAMBANG MALANG - Gilang Sandhubaya; Ayu Fitriatul ‘Ulya; Rulli krisnanda; Dewi Indriani (Bogor Hospitality Journal, 2023)
The Ministry of Tourism and Creative Economy has issued directives to regions in Indonesia to adhere to the CHSE protocol standards, namely Cleanliness, Health, Safety & Environment Sustainability, in order to curb the spread of Covid-19 in Indonesia, particularly in the tourism sector . The purpose of implementing CHSE-based tourism destination management is to formulate operational tourism strategies that can be implemented in affected areas, including South Malang such as Balekambang Beach in Malang Regency. The research method used is SWOT analysis using the ISTA (Indonesia Sustainable Tourism Award) assessment indicators. Regulated by Minister of Tourism Regulation No. 14, ISTA outlines sustainable destinations. Balekambang Beach will be evaluated using ISTA assessment indicators to identify existing criteria in terms of infrastructure, organization, and supporting facilities. Any deficiencies can be developed or improved upon. The analysis of strengths, weaknesses, opportunities, and threats is based on SWOT analysis. The tourism management at Balekambang Beach falls within quadrant 1 (+, +), indicating a strong and progressive situation. The necessary strategy to be implemented is to maintain and create operational patterns based on sustainable health protocols. The implementation of an aggressive strategy (SO) focusing on marketing and broad segmentation is still feasible, although Balekambang Beach has a low level of competitiveness.